Bank Efficiency and Oil Price Volatility: A View from the GCC Countries - Ammar Jreisat; Somar Al-Mohamad (Emerging Science Journal, 2022)
The study investigates the banks' efficiency in the Gulf Cooperation Council (GCC) countries' members (GCC). The efficiency of the banking sector is a cornerstone in the financial development of a country. It has also become a prominent label in both economic and financial lexicons due to the lucid importance of the financial intermediation function it provides. The banking industry is considered the backbone of the financial system in oil exporting countries of the GCC region. In general, the advancement and stability of the banking sector are inextricably related to the total economic output as measured by the GDP and to the stability of the financial system in particular. This study aims to evaluate how efficient banking is in the six countries of the GCC bloc, and to assess the effect of the oil price shock in 2014 on the bank’s efficiency in these countries. This study employs the 2-stage Data Envelopment Analysis (DEA) methodology for this aim. This model assigns efficiency scores for GCC banks over a period of time from 2008 to 2016 in the first stage. The second stage of the model regresses the aforementioned efficiency scores against a variety of financial and macroeconomic variables to depict the main determinants of bank efficiency and to assess the banking sector's resilience to global shocks as well as to macroeconomic conditions. The empirical outcomes of this study indicate that the global financial crisis (GFC) in 2008 and the oil price shock in 2014 had a significant negative impact on the efficiency scores of the GCC banks. The findings also show that domestic macroeconomic indicators have a greater impact on bank efficiency than institutional or bank-specific variables.JEL Classifications: E6, E44, Q4, G21 Doi: 10.28991/ESJ-2022-06-03-07 Full Text: PDF